Strategi Distribusi Pangan Menggunakan Neraca Bahan Makanan (Studi Kasus di Provinsi Jawa Tengah) - Purbayu Budi Santosa; Darwanto Darwanto (Jurnal Dinamika Ekonomi & Bisnis, 2017)
Food security can be realized with a food system that is well managed. This can be reflected from well food distribution system between regions. Indicators of food security is inadequate needs of areas experiencing food deficits. This study aimed to carry out mapping the area of food surpluses and deficits in order to achieve food security. The analysis tool used is the balance of Foodstuffs (NBM) which is used to obtain a surplus and food deficit through calculation of the amount of food production and consumption in the region.